Cockeyed Education: A Case Method Primer - Giordano, Gerard (Rowman & Littlefield Publishers, 2010)
Should educators pay students? Should they make them wear sunglasses, regulate their clothing, allow them to bring animals into classrooms, discourage them from playing videogames, or transform their schools into gymnasiums? These are some of the suggestions that Cockeyed Education examines. This book enables readers to differentiate substantive from cockeyed suggestionsfor improving schools.. It directs them to the suggestions that scholastic experts, politicians, and members of the public have made. Additionally, it introduces them to the case method. It helps them apply this analytical technique to events that range from early Chicago schooling to the 2009 economic stimulus package.